Effect of Berry Polyphenols on Glucose Metabolism: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Rambaran, Theresa F (Curr Dev Nutr, 2020)
The effect of berry polyphenols on glucose metabolism has been evaluated in several studies; however, the results are conflicting. A systematic review and meta-analysis was therefore conducted to evaluate the effect of berry polyphenol consumption on glucose metabolism in adults with impaired glucose tolerance or insulin resistance. PubMed/MEDLINE, Cochrane Central Register of Controlled Trials, CINAHL (EBSCO), and Scopus were searched for randomized controlled trials published by June 2019. Of the 3240 articles found, 21 met inclusion criteria. Study-specific effects were calculated as mean differences, which were pooled using fixed-effect, inverse-variance weighting. Overall, berry polyphenol consumption did not have a clear effect on biomarkers of glucose metabolism compared with placebo or no treatment. Although some analyses showed statistically significant effects, these effects were too small to be of clinical relevance. The review protocol was registered in the PROSPERO International Prospective Register of Systematic Reviews as CRD42019130811.